The investigation of bio-preservative properties in Plukenetia volubilis L. (Sacha inchi) seeds protein extract for food spoilage prevention - Md Zin, Noor Hasniza; Abdul Wahab, Widya; Ahmad, Mohammad Norazmi; Sapak, Zaiton; Azahar, Noor Suhana (The Malaysian Society of Applied Biology, 2024)
The importance of food quality and safety has long been recognized by the food industry to cater to food spoilage. Food spoilage is caused by the loss of food quality from its original organoleptic qualities due to chemical and biological spoilage processes that may impact customer acceptance. This research aimed to evaluate the potential of Sacha inchi seeds protein as a multifunctional food preservative in controlling chemical (oxidation) and biological (microbial and protease activity) food spoilage. The antioxidant capacity revealed that the Sacha inchi seed protein has 73.72 ± 0.70% inhibition towards oxidation with the total phenolic content detected at the concentration of 463.13 ± 0.51 μg/mL in the protein extract. The tested food spoilage bacteria (Escherichia coli and Micrococcus luteus) and fungus (Colletotrichum gloeosporioides) were susceptible to Sacha inchi seed protein showing its potential antimicrobial properties. The Sacha inchi protein extract (46.65 μg/mL & 23.28 μg/mL) shows a significant inhibition for E. coli (30.5 mm) and M. luteus (33 mm), respectively, which indicated its effectiveness. Sacha inchi seed protein also displayed potential antifungal activities by suppressing the growth of C. gloeosporioides at inhibitory concentration percentages (IC%) of 1.5±0.12%, 5.85±3.89% and 5.90±1.98% after 2, 3 and 4-days of incubation, respectively. The caseinolytic plate assay revealed that Sacha inchi seed protein showed inhibition of trypsin digestion on casein with reduced inhibition diameter from 1.9±0.00 cm (negative control) to 1.05±0.00 cm. Following the effective protein separation by SDS-PAGE, zymography analysis revealed that a prominent protein band at 25 kDa showed protease inhibitory activity. This research contributes insights into the potential application of Sacha inchi seed extract as a bio-preservative in the food industry to combat food spoilage and it is aligned with SDG 2 for zero hunger